Violence in the Viking World: New Bioarchaeological Evidence - Joerg Baten; Giacomo Benati; Anna Kjellström (European Historical Economics Society (EHES), 2021)
Vikings – the Scandinavian seafaring populations that dominated the North Seas between the eighth and eleventh centuries CE – are usually described as pirates and warriors living in a highly aggressive society. But was this really the case? How violent were the Vikings among themselves? In this study, we compare the share of cranial trauma and weapon wounds that we can observe for several skeletal samples of Scandinavian societies with other European medieval populations (excluding military and warrior populations). This is the first time that Viking violence can be empirically compared with a standardised European sample of 2,379 skeletons. We find that Scandinavian rural and urban communities were characterised by remarkably low levels of interpersonal violence, relative to other Europeans. Given the lack of strong centralisation of states, police deterrence mechanisms and low literacy, the best possible explanation for this pattern may be found in the relatively high gender equality that characterised Viking rural communities – as attested by significant health levels of female skeletal remains, relative to males. Low population density, specialisation in cattle farming and extensive grazing entailed a more significant role for women in household economies. This, in turn, may have had an ameliorative effect reducing the motivation for violence in general. This discovery adds empirical evidence to recent literature in criminology and gender economics, indicating a nexus between gender inequality and homicide rates. We provide new explanations on how societies have solved the problem of violence and open new avenues of research on the use of archaeological proxies for addressing important topics in societies today.
Keywords: N00; N13; N33; 330; violence; early medieval; state formation; gender equality; vikings; Scandinavia